Pericardial salmonella with cardiac tamponade and ventricular wall rupture: A case report. (May 2016) - Chand, Gaurav; Jhaj, Ruby; Sanam, Kumar; Sinha, Prabhat; Alexander, Patrick
Abstract: Introduction: Non-typhoidal Salmonella (NTS) is mostly restricted to gastroenteritis; however, we report a case of Salmonella pericarditis complicated by tamponade and spontaneous ventricular wall rupture. Case presentation: A 67-year-old male presents to the Emergency Department with complaints of fevers, chills and body aches. A chest radiograph displayed an infiltrate and an electrocardiogram suggested acute pericarditis. An echocardiogram revealed a small pericardial effusion without tamponade. Broad-spectrum antibiotics were initiated until Salmonella was discovered in blood cultures. The hospital course was complicated by sudden decompensation, and a repeat echocardiogram displayed a large effusion with constrictive physiology. During a pericardial window, the tissue was noted to have a thickened appearance with a complex effusion. The following day, the patient developed increased chest tube drainage, hypotension and acidosis, requiring an emergent sternotomy. The right ventricle was friable and had spontaneously ruptured. After ventricular repair and pericardiectomy, the tissue was sent for cultures and pathology. The specimen revealed Salmonella enteriditis. Treatment with ceftriaxone and ciprofloxacin was initiated. On postoperative day four, the patient was successfully extubated. Repeat blood cultures were negative. Discussion: In our review of literature, only 19 cases of NTS pericarditis have been reported. Prior to our case, salmonellosis resulting in ventricular rupture has been reported once. Early diagnosis and treatment is crucial in minimizing morbidity and mortality. Clinical suspicion based on electrocardiogram and hemodynamic assessment is critical in suspecting pericardial effusion in a patient with nonspecific symptoms and Salmonella bacteremia. The key to recovery involves aggressive treatment, including pericardiectomy and antibiotic treatment. Highlights: Patient with Salmonella pericarditis complicated by tamponade and ventricle rupture. Salmonella enteriditis bacteremia secondary to a cardiac source. Promptly diagnose and treat patients with hemodynamic compromise from tamponade. Consider a cardiac etiology when faced with Salmonella bacteremia.